A fistful of dollars: Transmission of global funding shocks to EMs - Shekhar Hari Kumar; Aakriti Mathur (Graduate Institute of International and Development Studies, 2020)
In this paper, we study transmission of global funding shocks to emerging economies (EMs) from the perspective of interbank markets. Money markets enable banks to engage in risk-sharing against liquidity shocks and are sensitive to global funding conditions. Accordingly, we first show that interbank rates better reflect the magnitude of transmission of foreign liquidity shocks to EMs as compared to benchmark short-term bond yields. Next, we disentangle the transmission into its various channels, focusing in particular on two pull factors associated with the domestic banking microstructure: dependence on wholesale funding and share of foreign banks. Our results indicate that money market rates in EMs react to global shocks, and that in particular dependence on wholesale funding has a significant role to play. Finally, we provide evidence that tools of macro-prudential policy like reserve requirements can help alleviate liquidity shocks to the EM banking system, weakening this global transmission.
Keywords: E43; E44; E52; E58; F42; G15; G21; 330; International transmission of liquidity shocks; quantitative easing; wholesale funding; interbank rates; macro-prudential policy; reserve requirements